Effects of swimming training on tissue glycogen content in experimental thyrotoxic rats - Paulino Ribeiro, Luiz Fernando [UNESP]; Teixeira, Inaian Pignatti [UNESP]; da Silva, Glaucio Aparecido [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Costa Junior, Marcelo [UNESP]; Bertolini, Natalia Oliveira [UNESP]; Rostom de Mello, Maria Alice [UNESP]; Luciano, Eliete [UNESP] (Canadian Science Publishing, Nrc Research Press, 2012)
Thyrotoxicosis, a condition in which there is an excessive amount of circulating thyroid hormones, leads to reduced glycogen content in different tissues. In this study we analyzed the effects of aerobic swimming training on liver, heart, and skeletal muscle glycogen content in experimentally induced thyrotoxicosis. Wistar male rats were divided into euthyroid sedentary (ES, n = 12), euthyroid trained (ET, n = 11), thyrotoxic sedentary (TS, n = 12), and thyrotoxic trained (TT, n = 10) groups. Thyrotoxic groups received daily i.p. doses of T4 (sodium levothyroxine, 25 mu g/100 g body mass) through the experimental period, and trained groups swam for 1 h at 80% of the aerobic-anaerobic transition intensity, 5 days/week for 4 weeks. Heart and liver glycogen stores were similar to 30% lower in T4 treated compared with nontreated groups, but were not changed by training status. on the other hand, glycogen content in mixed fiber type gastrocnemius of TT was 1.5- to 2.3-fold greater than those in other groups, whereas no significant differences were found for the slow soleus muscle. Increased gastrocnemius but not soleus, liver, or heart glycogen indicates that in mild long-term thyrotoxicosis chronic swimming affects glycogen stores in a tissue-specific manner.
Keywords: carbohydrate; exercise; hyperthyroidism; thyroid hormones; training; muscle; glycogen